Factors affecting development of Clostridium difficile infection in hospitalized pediatric patients in the country Georgia - Iuri Migriauli; Vakhtang Meunargia; Ivane Chkhaidze; Giorgi Sabakhtarishvili; Kakha Gujabidze; Maia Butsashvili; George Kamkamidze (BMC Research Notes, 2018)
Abstract Objective Main aims of our study were to investigate occurrence of Clostridium difficile among hospitalized pediatric patients in Georgia and examine risk factors for the development of C. difficile infection. During our study we tested and piloted the real-time PCR diagnostic systems for rapid and simultaneous identification of C. difficile and number of other pathogens in our facility settings. A cross-sectional study has been performed in children less than 18 years of age in two pediatric hospitals in Georgia, between May 2016 and December 2017. Stool specimens negative by the conventional bacteriology analysis were analyzed for the presence of C. difficile and several viral and protozoa pathogens using enzyme immune assay and polymerase chain reaction. In total samples from 220 hospitalized children with gastroenteritis symptoms were analyzed in this study. Results The average age of the study participants was 4.7 years. Overall 23 children were identified positive for C. difficile (10.5%). Antibiotic exposure within 2 months preceding the onset of diarrhea was associated with an increased risk of C. difficile infections. The risk was greatest with cephalosporins, followed by penicillins, carbapenems and macrolides. Clostridium difficile is an important cause of healthcare-associated diarrhea in pediatric population of Georgia.